PEMBEKALAN KETRAMPILAN VIDEO EDITING MENGGUNAKAN VEGAS PRO UNTUK ANAK ASUH UPT RUMAH PENGASUHAN ANAK WILOSO PROJO PEMERINTAH KOTA YOGYAKARTA - Catur Iswahyudi; Erna Kumalasari Nurnawati; Edhy Sutanta; Rosalia Arum Kumalasanti (LPPM IST AKPRIND Yogyakarta, 2019)
Along with the development of the globalization era, Information and Communication Technology (ICT) is also growing rapidly and has become a primary need for many people. Currently the community is familiar with the use of ICTs, including in the form of video use. Video is used to record daily activities, formal activities and also become a means of actualizing themselves in social media. This activity aims to introduce video editing skills for foster children of UPT Wiloso Projo Children's Care Center, Yogyakarta City Government. The activities are carried out in the form of socialization, scheduled workshops, and mentoring that are carried out by lecturers with the assistance of student activity partners. Participants practice what is learned using computer. Community Service Activities conducted for children at UPT Wiloso Projo Children's Care Center produce video content created and edited by workshop participants. These skills are expected to be applied in everyday life; both for personal profiles and for professional purposes.